Construction of a self-rated Malaysian emotional intelligence scale - Ahmad Tharbe, I.H.; Ng, K.M.; Sumari, M. (2015)
This study aims to develop and validate a self-rated emotional intelligence scale for Malaysian population based on the Mayer and Salovey’s framework of emotional intelligence. A total of 405 students and working adults participated in this study. Factor analysis and reliability analyses were carried out to determine the construct validity and internal consistency of the Self Rated Malaysian Emotional Intelligence Scale (SRMEIS). The factor analysis showed that four major constructs emerged, in accordance with Mayer and Salovey’s domains of emotional intelligence with factor loadings more than 0.4. The reliability analysis resulted in a cronbach’s alpha value of 0.922 for SRMEIS. The domains of Emotional Perception and Expression, Emotional Facilitation of Thinking, Emotional Understanding and Emotional Management yielded cronbach’s alpha value of .859, .868, .683 and .893 respectively. These findings confirm the validity and reliability of SRMEIS as a self-rated psychometric instrument to measure emotional intelligence.